Dose-Dependent Application of Straw-Derived Fulvic Acid on Yield and Quality of Tomato Plants Grown in a Greenhouse - Zhang, Peijia; Zhang, Hongjia; Wu, Guoqing; Chen, Xiaoyuan; Gruda, Nazim; Li, Xun; Dong, Jinlong; Duan, Zengqiang (Frontiers in Plant Science, 2021)
Fulvic acids are organic compounds widely distributed in soils, and the application of fulvic acids is thought to increase crop yield and quality. However, the effects vary among various sources and doses of fulvic acids, environmental and growth conditions of crops. Here, we investigated the effects of bioresource-derived (corn straw) fulvic acids on plant production and quality of tomato plants, and soil chemical properties in soil cultures whilst the experiments of seed germination and hydroponic were conducted to explore the underlying mechanism. Base dressing with 2.7 g kg-1 increased the yield of tomato by 35.0% at most by increased fruit number. Fulvic acids increased the concentrations of minerals like Ca, Fe and Zn, the concentrations of citric acid, malic acid and some amino acids in berries of tomato, but did not affect the concentrations of soluble sugars and aromatic substances in tomato fruits. Similarly, fulvic acids at 80-160 mg L-1 increased germination rate, growth vigor and radicle elongation of tomato seeds whilst it increased plant biomass, concentrations of nutrients and root length of tomato plants in hydroponics to the greatest extent as a general. The increases in yield and quality could be attributed to the improvement in root growth and thus increased nutrient uptake. In addition, the base application of fulvic acids improved soil cation exchange capacity and soil organic matter to an extent. In conclusion, base dressing and addition into solution of fulvic acids at moderate doses facilitate root growth, nutrient uptake and thus vegetable production and quality, and therefore fulvic acids can be an effective component for designing new bio-fertilizers for a sustainable agricultural production.